PENERAPAN GRASI DI INDONESIA SEBAGAI HAK PREROGATIF PRESIDEN TERHADAP TERPIDANA KASUS NARKOBA - Amelia Riska Permatasari (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2013)
AbstractThe purpose of this study was to determine the extent of the application of clemency granted to convicted drug cases in Indonesia. Clemency is the prerogative of the president of which is forgiveness in the form of change, mitigation, reduction or elimination of the implementation of the convicted criminal by the President. The scope of clemency by Law no. 5 of 2010 on the amendment of Law no. 22 of 2002 on the pardon of all court decisions that have permanent legal force. The verdict is the death penalty, life imprisonment or imprisonment for a two-year low. Given the number of convicted drug cases in Indonesia to seek a pardon, humanitarian considerations may be one reason for granting clemency to death row drug cases. However, the granting of pardons should be right given to inmates who do have a strong humanitarian reasons.Keywords: clemency, presidential prerogative, drugs.